Pengaruh Supervisi Akademik Kepala Sekolah Terhadap Kinerja Guru - Imam Setiawan (Journal of Innovation in Teaching and Instructional Media, 2025)
This study investigates the influence of principals' academic supervision on teacher performance. This study uses a Systematic Literature Review (SLR) approach. One of the main tasks of school managers is academic supervision, which has a direct impact on the quality of learning and teacher professionalism. This study analyzed 15 relevant national journal articles. These articles were obtained through a careful search of Google Scholar and SINTA. The results show that principals' academic supervision has a positive and significant impact on teacher performance, both directly and through mediating variables such as leadership, school culture, and work motivation. This article emphasizes how important it is for principals to be actively involved in implementing continuous, planned, and organized academic supervision if they want to improve the quality of education.